2012
DOI: 10.3357/asem.3195.2012
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Oxygen Pressure Following Whole-Body Vibration at Altitude

Abstract: We contribute the lack of effect to the low vibration intensity used in this study. Since this vibration intensity was higher than experienced by helicopter crews during flight, we conclude that whole-body vibration does not contribute to hypoxia during high-altitude operations in helicopters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…Overall, 56 original articles reporting data on ABGs under hypobaric hypoxic conditions among healthy volunteers met inclusion criteria. A Galbraith plot including those 56 studies identified 3 visual outliers, which were excluded (eResults and eFigure 1 in Supplement 1).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Overall, 56 original articles reporting data on ABGs under hypobaric hypoxic conditions among healthy volunteers met inclusion criteria. A Galbraith plot including those 56 studies identified 3 visual outliers, which were excluded (eResults and eFigure 1 in Supplement 1).…”
Section: Resultsmentioning
confidence: 99%
“…In total, 53 studies reporting 115 group ascents to altitudes between 1524 m and 8730 m were included in the aggregated data analysis. Two of those studies (3.8%) were not incorporated into the forest plot due to missing measurements of variance.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations